Influence of Phonological Awareness, Morphological Awareness and Non-Verbal Ability on Dictated Spelling In Malayalam - K. ABDUL GAFOOR and REMIA K R (Scholars World, 2013)
This study examined the collective influence of phonological awareness, morphological awareness and non-verbal ability on dictated spelling in Malayalam using multiple regression analysis. Data was obtained via representative sample survey on lower primary students in grade 2 and 3 of 11 Lower Primary Schools in Kerala. One year after measuring predictor variables in grade 2, dictated spelling was appraised in Grade 3. All the three first order r’s of dictated spelling with the predictors were significant and positive. However, non-verbal ability has no significant influence on dictated spelling, independent of the Morphological Awareness and Phonological Awareness. Morphological Awareness (18.22%) contributed more than Phonological Awareness (14.71%) to the dictated spelling in Malayalam. Together, the two variables account for nearly 1/3 of variance in students’ dictated spelling. The result suggests adoption of a linguistic-component-based-approach that enhances phonological awareness and morphological awareness, to strengthen spelling ability in early grades.